2020
DOI: 10.1371/journal.pone.0233878
|View full text |Cite
|
Sign up to set email alerts
|

Different wheat cultivars exhibit variable responses to inoculation with arbuscular mycorrhizal fungi from organic and conventional farms

Abstract: The present study aimed to investigate the effects of arbuscular mycorrhizal (AM) fungal communities originating from organic and conventional agriculture on wheat growth and yield. Six different spring wheat cultivars released in different years in north and central European countries were considered. We hypothesised that AM fungal inoculum collected from organic agricultural fields would elicit a greater positive growth response than inoculum collected from conventional agricultural fields; and that older cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
(71 reference statements)
4
18
0
1
Order By: Relevance
“…It can be speculated that host genotype determined the fungal mycobiome recruited from the rhizosphere soil into the potato roots. Furthermore, a similar, consistent and weak, yet significant, effect of genotype on bacterial community composition in plant roots was observed in previous studies [61], [62], [63].…”
Section: Discussionsupporting
confidence: 89%
“…It can be speculated that host genotype determined the fungal mycobiome recruited from the rhizosphere soil into the potato roots. Furthermore, a similar, consistent and weak, yet significant, effect of genotype on bacterial community composition in plant roots was observed in previous studies [61], [62], [63].…”
Section: Discussionsupporting
confidence: 89%
“…It can be speculated that host genotype determined the fungal mycobiome recruited from the soil into the potato roots. Furthermore, a similar, consistent and weak, yet significant, effect of genotype on bacterial community composition in plant roots was observed in previous studies [70][71][72].…”
Section: Effect Of Cultivarssupporting
confidence: 88%
“…There is, however, evidence that plant breeding, which significantly changes the crop genetic makeup, affects also the host-AMF interaction [ 35 ]. In wheat, for example, it has been demonstrated that cultivars differ in terms of AMF root colonization intensity, nutrient uptake, growth response and root-inhabiting AMF community composition [ 36 38 ]. Information is, however, lacking about the role of the genetic makeup of the host plant on the structure of root-inhabiting AMF communities in wild plant populations.…”
Section: Introductionmentioning
confidence: 99%